Anterior Referencing versus Posterior Referencing in Total Knee Arthroplasty - Fokin, Alexander A.; Heekin, Richard D. (The Journal of Knee Surgery, 2014)
Appropriate femoral component positioning and sizing is essential for proper kinematic function in total knee arthroplasty (TKA). Anterior or posterior referencing (AR or PR) are two major techniques for setting center of rotation and for balancing the sagittal plane of the arthroplasty. Both techniques have advantages and disadvantages. Minimally invasive surgical (MIS) TKA has added yet another aspect to intraoperative techniques and postoperative outcomes. A total of 100 consecutive patients undergoing unilateral MIS TKA were prospectively randomized to either AR or PR. Knee Society Scores, range of motion, SF-12, and strength testing by Cybex dynamometer were evaluated at standardized intervals postoperatively for 2 years. There were no statistically significant differences in surgical (incision length, surgical release, blood loss, surgical time, and length of stay) or clinical outcomes between two groups at all postoperative intervals (2 and 6 weeks, 3 and 6 months, and 1 and 2 years). Results demonstrate that both AR and PR are effective and can be used successfully during MIS TKA.
Keywords: anterior referencing; posterior referencing; knee arthroplasty